Pseudomonas aeruginosa and Its Pathogenicity - Nida Nur Urgancı; Nazife Yılmaz; Gamze Koçer Alaşalvar; Zeliha Yıldırım (Turkish Journal of Agriculture: Food Science and Technology)
Pseudomonas aeruginosa, belonging to the Pseudomonadaceae family, is Gram-negative, rod-shaped, motile, aerobic, endospore negative, oxidase and catalase positive. It is widely found in nature and isolated from soil, plants, water and animals. It can grow rapidly on the surface of the food and form oxidized products and mucous substances. P. aeruginosa, one of the leading foodborne pathogens, causes important concerns in food safety due to being a source of contamination, causing food poisoning and antimicrobial resistance in animals, forming biofilms and difficulties in preventing biofilms. In this review, information on history, microbiological, cultural and biochemical characteristics, virulence factors and pathogenicity of P. aeruginosa are given. In addition, infections caused by P. aeruginosa and its presence in food are described.